Phagocyte-mediated killing of Candida tropicalis - Lindemann, R A; Franker, C K (Mycopathologia (1975), 1991)
Human peripheral monocytes (MO), neutrophils (PMN), and lymphocytes (PBL) were tested for their ability to kill Candida tropicalis. With incubation times between 30 min and 2 h, unstimulated MO and PMN, but not PBL, were efficient killers of C. tropicalis. Both leukocyte subsets were able to kill at minimum 2.5:1 effector to target ratios. Pre-incubation of MO for 24 h with interferon-gamma or tumor necrosis factor (TNF) increased their ability to kill yeast targets. TNF alone had no effect on C. tropicalis targets at concentrations up to 1000 U/ml. PBL activated for 4 d with interleukin-2 did not kill yeast targets. PMN exhibited more cytocidal efficiency per cell than MO in these assays. Direct contact of effectors and targets was required; no significant killing by PMN or MO supernatants was measured. PMN-mediated killing, but not MO killing, was inhibited by a mixture of catalase and superoxide dismutase suggesting that oxygen-dependent killing mechanisms were partially responsible for candidacidal activity.